ANALISIS PENGARUH CAMPURAN FLY ASH, SIKAMENT NN DAN SERBUK CaCO3 PADA BETON TERHADAP NILAI KUAT TEKAN AWAL BETON - Sofian, Arsito; Ramadhan, Aziz Bayu; Arrosyid, Azwar (Jurnal Proyek Teknik Sipil, 2019)
Nowadays, the use of portland cement in concrete can pollute the environment because the pollution caused by portland cement factories. Therefore, the enviromentally friendly materials which have the properties of portland cement are needed to reduce the proportion of portland cement and at once can improve the quality and the characteristics of concrete. This study aimed to determine the increase of  ealry compressive strength of concrete with added materials Sikament NN and fine powder of CaCO3 and fly ash. The innovation of admixtures that we use in order to subtitute the proportion of some portland cement are CaCO3 powder as type C admixture (accelerator) and Fly Ash type C with the precentage of each is 10% and 30% of the total weight of portland cement. In order to improve the workability of concrete, we use type E admixture (accelerator and water reducer) with the name of product is Sikament NN by 1,5% of the total weight of portland cement. The Mixing method used is  SNI-03-6468-2000. The desired compressive strength of concrete with added materials CaCO3 powder, fly ash and sikament NN at age 1 day in mix design is 15,31 MPa and the slump value is 22,5 cm. the result showed that compressive strength of concrete at age 1 day with those admixtures is 17,19 MPa and the slump values is 23 cm. From the datas we know that concrete with added materials CaCO3 powder, fly ash and sikament NN can increase the early compressive strength about 12,3 %.